Temperature-sensitive mutant of adenovirus type 2 blocked in virion assembly: accumulation of light intermediate particles. - D'Halluin, J C (1978)
A temperature-sensitive mutant of human adenovirus type 2, ts112, was isolated and characterized, ts112 was blocked in a late function required for virus maturation. At restrictive temperature, it accumulated light precursor particles that were able to mature into infectious virions upon temperature shift-down. Use of a mild extraction procedure and a reversible fixation by a cleavable diimido ester permitted the isolation and analysis of these labile intermediates in the adenovirus assembly. These accumulated particles had a sedimentation coefficient of about 600S and a buoyant density of 1.315 g/cm3 in CsCl. They contained a DNA fragment of 7--11S and two nonvirion proteins having molecular weights of 50,000 (50K) and 39.000 (39K), respectively. They resembled in composition and morphology the light intermediate particles found in wild-type adenovirus 2, which were identified as precursors of heavy intermediates, preceding the young virions. The ts112 lesion was apparently located at the exit of either the 50K and/or 39K proteins and at the entry of viral DNA.